(untitled) (CAHIERS MAGELLANES-NS, 2024)
Abstract— Use of public transport has been in focus for very long time owing to its obvious benefits. Still around the globe, a large share of urban and inter-urban transport system is out of reach for person with disabilities. Wheelchair users find it difficult to use buses, even low-floor ones. Wheel chair ramps deliver a decorous, identical approach to entering a low-floor bus. Wheel chair ramps are a platform generally constructed in aluminium that can be deployed manually or automatically for wheelchair passenger for on boarding. It is necessary for it to be lightweight yet highly durable ensuring the fuel efficiency for automobile operators. This study discusses a conceptual manually operated foldable design for wheel chair ramp. For this design, a sandwich structure is designed along with use of composite for a designated loading requirement. This will be done to convert the conventional design for light weighting yet durable design. Design evaluation is done using FEA for static structural analysis. Physical testing will be conducted to investigate strength requirement and mechanical behaviour using UTM. FEA results are compared to physical test results under this study.